Study on quality and milling recovery of different varieties of rice at varying degree of polishing under Khumaltar condition - Thapa, MJ; Shrestha, MB; Karki, R; Bhattarai, CM (Agronomy Journal of Nepal, 2013)
In Khumaltar, under NARC, rice varieties; Khumal-4, Khumal-8 and Radha-32 as slender varieties and Khumal-11, Taichung, Chainung-242 as bold varieties were studied for assessing their qualitative traits during 2006-08. These were milled in Satake Sheller and polished in Yamamoto polisher at different degree of polishing (0, 4, 8 and 12%). The mean milling recovery (73.4%), head rice (84.8%), broken rice (15.1%), protein (7.71%), ash (0.84%) and fat (1.34%) were recorded from the experiments. Among them, milling recovery, head rice, protein, fat, and ash were found significant (P < 0.05) with increasing degree of polishing. These attributes (head rice, protein, ash, and fat) were recorded increased at 8 and 4% degree of polishing compared to that of 12%. However, for 12% degree of polishing the milling recovery, head rice, protein, fat and, ash content were low as against 4 and 8% degree of polishing. The study showed that nutritional value of protein, fat and, ash contents were found high at 4 and 8% degree of polishing compared to that of 12%. Similarly, the percentage of head rice also increased at 4 and 8% than at 12% degree of polishing. The percentage of broken rice was also increasing with the increasing degree of polishing. Therefore, the result could be concluded that lowering the degree of polishing from 12% to 8% to 4% for both slender and bold rice could be increased rice stock by 4% in country’s total rice production. Hence, the result of this study would help strengthen the food and nutritional security and improve quality of rice in the country as well. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7523 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.88-92